Adverse pregnancy, delivery and neonatal outcomes across different advanced maternal ages: A population-based retrospective cohort study - Alexandre Machado-Gédéon; Ahmad Badeghiesh; Haitham Baghlaf; Michael H. Dahan (Elsevier, 2023)
Objective: Characterize the risk for adverse pregnancy, delivery and neonatal outcomes among different advanced maternal ages (AMA). Study design: We conducted a population-based retrospective cohort study using data from the Healthcare Cost and Utilization Project-Nationwide Inpatient Sample to characterize adverse pregnancy, delivery and neonatal outcomes among different AMA groups. Patients aged 44-45 (n = 19,476), 46-49 (n = 7528) and 50-54 years (n = 1100) were compared to patients aged 38-43 years (n = 499,655). A multivariate logistic regression analysis adjusted for statistically significant confounding variables. Results: With advancing age, rates of chronic hypertension, pregestational diabetes, thyroid disease and multiple gestation increased (p < 0.001). The adjusted risk of hysterectomy and need for blood transfusion substantially increased with advancing age, reaching up to an almost 5-fold (aOR, 4.75, 95 % CI, 2.76-8.19, p < 0.001) and 3-fold (aOR, 3.06, 95 % CI, 2.31-4.05, p < 0.001) increased risk, respectively, in patients aged 50-54 years. The adjusted risk of maternal death increased 4-fold in patients aged 46-49 years (aOR, 4.03, 95 % CI, 1.23-13.17, p = 0.021). Adjusted risks of pregnancy-related hypertensive disorders, including gestational hypertension and preeclampsia, increased by 28-93 % across advancing age groups (p < 0.001). Adjusted neonatal outcomes demonstrated up to a 40 % elevated risk of intrauterine fetal demise in patients aged 46-49 years (aOR, 1.40, 95 % CI, 1.02-1.92, p = 0.04) and a 17 % increased risk of having a small for gestational age neonate in patients aged 44-45 years (aOR, 1.17, 95 % CI, 1.05-1.31, p = 0.004). Conclusions: Pregnancies at AMA are at increased risk for adverse outcomes, particularly for pregnancy-related hypertensive disorders, hysterectomy, blood transfusion, and maternal and fetal mortality. Although comorbidities associated with AMA influence the risk of complications, AMA was demonstrated to be an independent risk factor for major complications, with its impact varying across ages. This data imparts clinicians with the ability to provide more specific counseling to patients of varied AMA. Older patients seeking to conceive must be counseled regarding these risks in order to make well-informed decisions.